Strategi Peningkatan Kesadaran Hukum Masyarakat Terhadap UU ITE Dan Pemanfaatan Teknologi Di Era Digital - Silviani, Yessi; Muthoharoh, Marfuatin; Julistina, Melly; Oktaria, Nenni; Putra, Adi Pramono; Ninosari, Devina; Khairil, Khairil; Sartika, Devi; Hermana, M.Arafat; Aprianto, Sandi (Jurnal Gotong Royong, 2025)
The increasing use of information and electronic technology has positive and negative impacts on daily life. Information and electronic technology facilitate communication, access to information, and business transactions. Digital utilization is one of the instruments of progress but also has the potential to become a problem if used inappropriately. Therefore, a legal product was made in the form of legislation which is a legal guideline that becomes an instrument for the implementation of Indonesia as a state of law, namely the Electronic Information and Transaction Law (ITE Law) which was issued as an effort to regulate the governance of information and electronic technology in Indonesia. In this context, the socialization activities to increase awareness of the importance of legal awareness and the rules contained in the ITE Law for the community in RT 23 Pematang Gubernur Village, this journal discusses the strategies applied in the Community Service Program (KKN) to increase community awareness of the Electronic Information and Transaction Law (ITE Law) and the use of technology in the digital era. The methods used include socialization, training, and the use of digital technology. Results showed an increase in community understanding of social media ethics and the risks of violating the law.